The Promise and Failure of Israeli-Palestinian Peace Process in 1990s: A Literature Review - V. M. Morozov; E. O. Shebalina; S. V. Melnikova (Vestnik MGIMO-Universiteta)
In 2023, the world marked 30 years since the start of the Oslo process, which sought to resolve the Israeli-Palestinian conflict. Given the ultimate breakdown of these negotiations, it is crucial to examine the evolution of academic research on this process, identifying its key themes and trends. This literature review focuses on both empirical and theoretical studies of the Oslo process, with a particular emphasis on research that investigates the reasons behind its failure. Such studies provide valuable insights for developing more effective models of negotiation and conflict resolution. Initially, the commencement of the Oslo negotiations was met with optimism in the academic community, with scholars highlighting the pivotal role of individual leaders in successfully launching the process. However, as the peace process faltered, the Israeli-Palestinian negotiations were analyzed through existing theoretical frameworks. Various scholars critically examined the Oslo Accords from the perspective of international law and highlighted economic factors that obstructed the path to a lasting peace. Other studies explored indirect influences on the peace process, such as public opinion and electoral dynamics, often employing Robert Putnam's “two-level games” theory. Nevertheless, these studies mainly address the immediate causes of the peace process’s failure and do not fully account for the underlying motivations driving the behavior of actors in the negotiations. Research into the deeper causes of the Oslo process’s collapse has highlighted socio-psychological barriers, such as the “conflict syndrome” and issues of ontological security. Scholars have investigated the roles of historical memory, collective trauma, and cultural identities in shaping negotiation outcomes. The rise of interdisciplinary approaches—combining insights from psychology, philosophy, and linguistics—has been essential for understanding the complex dimensions of this conflict. The diverse body of research and theories inspired by the Oslo peace process continues to influence the field of negotiation and conflict resolution studies, underscoring the enduring significance of this critical episode in diplomatic history.